Effect of Fire Exposure on the Properties of Self-Compacting Concrete reinforced by Glass Fibers - Aboud, Rawaa K.; Awad, Hadeel K.; Mohammed, Shatha D. (Engineering, Technology & Applied Science Research, 2024)
The optimal design of any structural elements requires examining all environmental risks, emergency accidents, and standard load cases. Exposure to fire is one of the most common safety threats. Nowadays wide developments are achieved in the field of concrete technology, therefore, experimental and theoretical investigations should be performed on the characteristics of such developed materials under different loading conditions. This study investigates the impact of fire exposure on the mechanical characteristics of self-compacting concrete, specifically compressive and tensile strength, modulus of elasticity, and stress-strain relation. The adopted fire exposure consisted of six steady-state temperatures (300, 400, 500, 600, 700, and 800°C) for one hour and a sudden cooling method. Four glass fiber volume fractions were adopted: 0, 0.5, 1, and 1.5%. The glass fiber volume fractions considered (0.5-1.5%) improved the mechanical properties investigated. Two states were detected for the effect of fire exposure. The effect of fire exposure was inversely proportional to fiber content in burning temperatures of 300-700°C, while the reduction in mechanical properties of 1.5% fiber content was greater than those of 0.5 and 1% when the temperature increased to 800°C. Furthermore, the addition of glass fiber changed the brittle mode stress-strain relation to semi-ductile for the non-burned and burned up to 600°C specimens, whereas a brittle behavior was detected when the temperature increased above 600°C. In general, a similar effect was noticed for all the glass fiber ratios considered regarding the slope of the stress-strain linear stage compared to the non-burned specimens, which was more salient when the burning temperature increased.